Studi Earning Management Dari Waktu Ke Waktu - Setiadi Alim Lim (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2012)
Prior studies suggests that earnings management can be distinguished on beneficial earning management or efficient earning management and opportunistic earning management. Although there is a positive motivation of earning management activity, that is the attempt manager to convey private information to shareholders and debtholders in order to reduce the informationgap that occurs in asymmetric information (beneficial or efficient earnings management , but the overall motivation of earnings management tends to be viewed negatively and is triggered by the interests of managers to maximize the interests of himself or the interests of business entities in order to maintain the market price of the stock at a specified value or the particular provisions ofa contract that is likely to prejudice the interests of external users of financial statements (opportunistic earnings management). Various manipulations of accounting scandals such as the case of Enron, WorldCom and others have influenced the way the public thinks, so begin to form the opinion that all the earnings management activities is a negative activity intended to defraud and must be fought. Earnings management can be performed with accrual oraccounting earnings management and real earnings management. Accrual or accounting earnings management have only a consequence of the accruals and will not affect cash flow. While real earnings management will affect cash flow and in some cases also affect accruals. There are some things you can do to reduce the practice of earnings management, which stricter accounting standards, the employment of an external auditor of a public accounting firm that has high integrity with long history and implementing good corporate governance practices. To detect accrual or accounting earnings management can be used several models in which one is best according to Dechow et al. (1995) is amodified Jones models. But Aminul Islam et al. (2011)stated that the Jones model of modification is not effective when applied in Korea and Bangladesh. Meanwhile, to detect the presence of real earnings management can use such a model of Roychowdhury (2006).